(untitled) (Politeja, 2019)
The article views the geographical area between the EU and Russian borders as a battle space of two, drastically different foreign policy and ideological approaches. The authors argue that in the years since the end of the Cold War, a unique surrogate of former clash of liberal and communist worlds emerged, leading to and underpinning current Hybrid Warfare, underway from Ukraine to Georgia. Its roots lay in the Russian interpretation of the Western attitude towards the East as Neo-colonialist. Relying on the income from its vast energy resources, Russia also tries to develop its version of so called “Soft Power”, used by the West in this region. Though in Russian hands, it is coupled with Moscow’s imperial experiences and resentments, and is becoming a mere element in Hybrid or “non-linear” war. Speaking retrospectively, the Eastern Partnership Initiative of the European Union can be seen as a response to Hybrid threats, posed by Russia against its Western and Southern neighbors. But the question is, whether EU foreign policy initiatives towards this area can and will be efficient and sufficient, if continued to be mostly defensive and limited within Soft Power mechanisms and philosophy, while Russia successfully combines those with traditional Hard Power know-how? The authors argue that in the long run, European or Euro-Atlantic Soft Power tool-kits, spreading Human Rightsbased culture farther in the East, will remain unmatched. But in order to prevail over the Russian revisionist policy here and now, the West, and, particularly, the EU need to re-evaluate traditional foreign policy options and come up with a more drastic combination of Soft/Hard Powers by itself. As the Georgian case shows, the European community should more efficiently use Conditionality and Coercive Diplomacy, combined with clearer messages about partners’ membership perspectives.